Parasitism of Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) on Spodoptera cosmioides (Lepidoptera: Noctuidae) at different temperatures - Cabezas G., Fernando; Melo, Mirtes; García, Mauro S.; Diez-Rodríguez, Gabriela I.; Nava, Dori E. (Revista Colombiana de Entomología, 2013)
Spodoptera cosmioides (Lepidoptera: Noctuidae) is a polyphagous pest that causes damage to various crops including those used in the production of biodiesel, such as castor bean (Ricinus communis), Barbados nut (Jatropha curcas), and Tung-oil tree (Aleurites fordii). One of the main biological control agents of lepidopteran pests are egg parasitoids of the genus Trichogramma. The influence of temperature on the performance of three strains (TRS13, TRS65 and TRS81) of Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) on eggs of S. cosmioides and thermal requirements were studied. The experiments were carried out at constant temperatures (18, 20, 22, 25 and 28) and 30 ºC, 70 ± 10% relative humidity and photoperiod of 14:10 (light: dark) hours. The development time of the three strains of T. pretiosum was inversely related to temperature rise. The temperatures affected the parasitoid emergency, being higher than 74% for each of the strains at 25 ºC. However, the temperatures tested did not affect the number of adults per egg and sex ratio. The lower temperature threshold (Tb) and thermal constant (K) were 11.21 ºC and 131.41 DD (degree-days) for strain TRS13, 10.73 ºC and 137.70 DD for TRS65 and 10.68 ºC and 138.70 DD for TRS81.